2021
DOI: 10.1136/sextrans-2020-054933
|View full text |Cite
|
Sign up to set email alerts
|

Patient delivered partner therapy for chlamydia infection is used by some general practitioners, but more support is needed to increase uptake: findings from a mixed-methods study

Abstract: ObjectivesPatient-delivered partner therapy (PDPT) describes the giving of a prescription or antibiotics by an index case with chlamydia to their sexual partners. PDPT has been associated with higher numbers of partners receiving treatment. In Australia, general practitioners (GPs) previously expressed negative views about PDPT. Health authority guidance for PDPT has since been provided in some areas. We investigated recent use and perceptions of PDPT for chlamydia among GPs in Australia.MethodsIn 2019, we con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Our website was developed in consultation with clinical staff. First, we administered a quantitative survey and conducted interviews with clinical staff to understand chlamydia management practices and inform the website design 21 34 35. Next, we conducted think-aloud interviews36 with clinical staff to assess the usability and acceptability of the prototype website, made modifications to the website and piloted it for 3 months in three practices in NSW and QLD.…”
Section: Methodsmentioning
confidence: 99%
“…Our website was developed in consultation with clinical staff. First, we administered a quantitative survey and conducted interviews with clinical staff to understand chlamydia management practices and inform the website design 21 34 35. Next, we conducted think-aloud interviews36 with clinical staff to assess the usability and acceptability of the prototype website, made modifications to the website and piloted it for 3 months in three practices in NSW and QLD.…”
Section: Methodsmentioning
confidence: 99%
“…The integration of peers into community engagement initiatives is often reported with high feasibility and acceptability [21][22][23]. The second type is patient-led interventions, which occurred in the form of patient navigation and patient notification in clinical settings [5,24]. While peer navigation and patient navigation are often used interchangeably in some literature [25,40], peers often refer to who have received some STIrelated or health intervention training and who can reach to a broad population within and beyond clinical settings.…”
Section: Key Pointsmentioning
confidence: 99%
“…7 Our recent research with Australian GPs found that they offer PDPT when they feel it is beneficial for their patient, even in the absence of health authority guidance. 16 Participants also reported they would like practical guidance for providing PDPT. 16 In this article, we give an overview of the process of offering PDPT as one option for undertaking partner management for chlamydia, including how to overcome potential challenges in its provision.…”
Section: Patient-delivered Partner Therapymentioning
confidence: 99%
“…16 Participants also reported they would like practical guidance for providing PDPT. 16 In this article, we give an overview of the process of offering PDPT as one option for undertaking partner management for chlamydia, including how to overcome potential challenges in its provision.…”
Section: Patient-delivered Partner Therapymentioning
confidence: 99%
See 1 more Smart Citation